Effect of different dental composite resins on the polymerization process - Rodrigues, T. P. [UNESP]; Rastelli, Alessandra Nara de Souza [UNESP]; Andrade, M. F. [UNESP]; Saad, José Roberto Cury [UNESP] (Maik Nauka/interperiodica/springer, 2009)
Dental composite resins possess good esthetic properties, and are currently among the most popular dental restorative materials. Both organic and inorganic phases might influence the material behavior, the filler particle features and rate are the most important factors related to improvement of the mechanical properties of resin composites. Thus, the objective of this study was to evaluate the effect of three different composite resins on the polymerization process by Vickers hardness test. The samples were prepared using three different composite resins, as follow: group I-P-60 (3M/ESPE); group II-Herculite XRV (Kerr), and group III-Durafill (Heraeus-Kulzer). The samples were made in a polytetrafluoroethylene mould, with a rectangular cavity measuring 7 mm in length, 4 mm in width, and 3 mm in thickness. The samples were photo-activated by one light-curing unit based on blue LEDs (Ultrablue III-DMC/Brazil) for 20 and 40 s of irradiation times. The Vickers hardness test was performed 24 h after the photo-activation until the standardized depth of 3 mm. The Vickers hardness mean values varied from 158.9 (+/- 0.81) to 81.4 (+/- 1.94) for P-60, from 138.7 (+/- 0.37) to 61.7 (+/- 0.24) for Herculite XRV, and from 107. 5 (+/- 0.81) to 44.5 (+/- 1.36) for Durafill composite resins photo-activated during 20 s for the 1st and 2nd mm, respectively. During 40 s of photo-activation, the Vickers hardness mean values were: from 181.0 (+/- 0.70) to 15.6 (+/- 0.29) for P-60, and from 161.8 (+/- 0.41) to 11.2 (+/- 0.17) for Herculite XRV composite resins, for the 1st and 3th mm, respectively. For Durafill composite resin the mean values varied from 120.1 (+/- 0.66) to 61.7 (+/- 0.20), for the 1st and 2nd mm, respectively. The variation coefficient (CV) was in the most of the groups lower than 1%, then the descriptive statistic analysis was used. The Vickers hardness mean values for Durafill were lower than P-60 and Herculite XRV composite resins for 20 and 40 s of irradiation time. The polymerization process was greatly affected by the composition of the composite resins.